Kolaborasi dalam Program Pengelolaan Sampah Organik melalui Pengolahan Berbasis Black Soldier Fly (Maggot) di Kota Padang - Mairahmah, Tarifa; Mubarak, Adil (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on collaborative organic waste management through black soldier fly (maggot) cultivation in Padang City, despite its significant potential to reduce organic waste generated by households and similar sources. The aim of this research is to analyze the forms of collaboration among stakeholders in an organic waste management program based on black soldier fly cultivation. A descriptive qualitative method was employed, using purposive sampling to identify key informants. Data were collected through interviews and documentation, then analyzed thematically. The findings reveal that communication serves as the primary mechanism reinforcing coordination among the Environmental Agency, CSR division of PT Semen Padang, and maggot cultivation groups. Although community outreach remains limited, the frequency of both formal and informal interactions has led to effective communication. Trust has developed through PT Semen Padang’s tangible support in the form of infrastructure, technical training, and mentorship, contributing to improved productivity and cultivation quality. Collaborative commitment is evident in the active roles of the Environmental Agency as regulator and facilitator, PT Semen Padang as a resource provider, and maggot groups as technical managers. Maggot cultivation has proven to be an innovative and economically valuable solution for organic waste reduction, aligning with the principles of sustainable environmental development.